Study of System Design Parameters for Space-Based Traffic Monitoring - Gabele, Martina; Baumgartner, Stefan; Krieger, Gerhard; Bethke, Karl-Heinz (International Radar Symposium (IRS), 2006)
This paper addresses the ground moving target indication (GMTI) performance and the impact of system design parameters on space-based multi-channel synthetic aperture radar (MSAR) systems as they suffer from the high speed of the radar platform leading to a wide spread clutter spectrum. Opposite to classical GMTI systems near future space-based SAR systems offer only few simultaneous channels and relatively low pulse repetition frequency (PRF). The impact of PRF, antenna size, antenna separations and number of channels on detection performance is studied. The analysis is based on a post-Doppler approach of the optimal processor.
DLR Import::2019-04-03